The Impact of Stone Quarrying On Socio Economic Status of Households in Nyakyibigi Ntungamo Municipality - Natweeta, Elvason (Kabale University, 2022)
A Research Report Submitted to the Faculty of Education in Partial fulfillment of the Requirement for the Award of the Degree of Bachelor of arts with Education of Kabale University.